Clinico-Laboratory Biomarkers of Systemic Inflammatory Response Syndrome Associated with Theileria annulata Infection in Cattle and its Prognostic Significance - Kumar Gupta, Kapil; Punia, Sunil; Dutta, Nishchal; Sudan, Vikrant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Bovine tropical theileriosis is an infectious multisystemic disease characterized by variable clinical signs including fever, lymphadenopathy, anaemia and sometimes haemoglobinuria. Present study was designed to assess the clinico-laboratory markers of systemic inflammatory response syndrome (SIRS) associated with bovine tropical theileriosis and its impact on prognosis of disease. Twenty two clinical cases of theileriosis were investigated for clinical and laboratory biomarkers of systemic inflammation. Clinical analysis revealed 86.36% of infected animals showed SIRS. Laboratory analysis revealed elevation in Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in 57.89% and 42.10% Theileria annulata infected cattle, respectively, while 31.57% animals showed both elevated NLR and PLR. Results of the study revealed the presence of systemic inflammation in majority of cases of bovine tropical theileriosis which exert effect on the prognosis of disease.